How writing works : a field guide to effective writing - Petelin, Roslyn (Crows Nest, NSW : Allen & Unwin, 2016)
Are you worried about your grip on grammar? Know you need to write better to get through uni or progress in your career? Or do you want to write professionally? We can all improve our writing: How Writing Works show us how.
This is Roslyn Petelin's promise: whether you already write reasonably well or not, this book will exponentially improve your writing...How Writing Works is a lively and practical introduction to the elements of grammar, sentence structure, and style that you need to write well. The book covers social media and writing for online publication, as well as the most common documents in the university and the writing-reliant workplace...How Writing Works should be on the desk of everyone who needs to write: students, professionals in all fields, and creative writers... 'A superb guide to great writing in the modern media era.' Phil Harding, journalist and broadcaster, London..'Whether you're a CEO or an intern, the ability to communicate clearly is your biggest asset. Petelin's expert advice in this book will accelerate your career'. Damian Kington, Global Head of Marketing, Liquidnet, New York.
Includes bibliographical references (pages 305-313) and index.
Keywords: Business writing; Authorship; English language -- Rhetoric; Written communication; Australian